Fabrication of core–shell porous nanocubic Mn2O3@TiO2 as a high-performance anode for lithium ion batteries1. Issue 35 (21st September 2015) - Chen, X. Q.; Lin, H. B.; Zheng, X. W.; Cai, X.; Xia, P.; Zhu, Y. M.; Li, X. P.; Li, W. S.
<x xml:space="preserve">Abstract</x> Core–shell porous nanocubic Mn2O3@TiO2 was synthesized and applied as an anode for lithium-ion batteries, exhibiting excellent cyclic stability and rate capability.